RUSSIAN-CUBAN GNSS SERVICE FOR MONITORING AND ANALYSIS OF GEOPHYSICAL PARAMETERS. - MARSHAIOV, D.; PONS RODRÍGUEZ, O.; BONDARENKO, YU.; SUVORKIN, V.; BEZRUKOV, I.; SERZHANOV, S. (Revista Cubana de Física, 2020)
This article describes the process of creation of the Russian-Cuban global navigation satellite systems (GNSS) service for monitoring and analysis of geophysical parameters based on station with co-located space geodetic instruments. The station will be located at the site of the Institute of Geophysics and Astronomy of the Republic of Cuba in Havana and will be equipped to conduct high-precision GNSS and meteorological observations. The GNSS service will provide time series of station coordinates, Earth orientation parameters, local tectonic plate movements, tropospheric delays, ionosphere and meteorological parameters and will become the basis for further expansion of the Cuban regional geodetic network.